206,977 newborn screening results reveal the ethnic differences in the spectrum of inborn errors of metabolism in Huaihua, China - Xiao, Gang; Feng, Zonghui; Xu, Chaochao; Huang, Xuzhen; Chen, Maosheng; Zhao, Min; Li, Yanbin; Gao, Yang; Wu, Shulin; Shen, Yuyan; Peng, Ying (Frontiers in Genetics, 2024)
Background: Inborn errors of metabolism (IEMs) are rare diseases caused by inherited defects in various biochemical pathways that strongly correlate with early neonatal mortality and stunting.Currently, no studies have reported on the incidence of IEMs of multi-ethnic groups in Huaihua,Methods: A total of 206,977 neonates with self-reported ethnicity who underwent IEM screening at Huaihua from 2015-2021 were selected for observation. Among them, 69 suspected IEM-positive neonates were referred for urine gas chromatography-mass spectrometry analysis, biochemical detection, next-generation sequencing, and Sanger sequencing.Results: Sixty-nine newborns were diagnosed with IEMs, with an overall incidence of 1:3,000. The two most common disorders were 2-methylbutyryl glycinuria (1:7,137) and phenylalanine hydroxylase deficiency (1:22,997). Moreover, the incidence of IEMs in the minority ethnic group (Miao, Dong, Tujia and Yao) (1:1,852) was markedly higher than in the Han ethnic group (1:4,741). Some ethnic features variants were identified; NM_001609.4:c.1165A>G in the ACADSB gene for Miao and Dong ethnic groups, NM_014251.2:c.852_855del in the SLC25A13 gene for Miao ethnic groups.This study revealed the IEM incidence within the minority ethnic groups is markedly higher than among the Han nationality and the gene variant spectrum is dramatically different in Huaihua, China. Hence, It serves as a theoretical reference for the screening and diagnosing of neonatal IEMs of multi-ethnic groups in the Huaihua area, and across China.